ADVERTISING ON THE MEDICAL TERMINOLOGY TEXTS IN RUSSIAN LANGUAGE AND ITS ANALYSIS - ARIPOVA, HALIMA (Центр Научных Публикаций (buxdu.uz), 2021)
The article provides an overview of medical terminology and ideas on the role of medical terminology in advertising texts. In addition, the role of medical terminology in Russian advertising texts was analyzed using examples